CoGraphNet for enhanced text classification using word-sentence heterogeneous graph representations and improved interpretability - Pengyi Li; Xueying Fu; Juntao Chen; Junyi Hu (Scientific Reports)
Abstract Text Graph Representation Learning through Graph Neural Networks (TG-GNN) is a powerful approach in natural language processing and information retrieval. However, it faces challenges in computational complexity and interpretability. In this work, we propose CoGraphNet, a novel graph-based model for text classification, addressing key issues. To overcome information loss, we construct separate heterogeneous graphs for words and sentences, capturing multi-tiered contextual information. We enhance interpretability by incorporating positional bias weights, improving model clarity. CoGraphNet provides precise analysis, highlighting important words or sentences. We achieve enhanced contextual comprehension and accuracy through novel graph structures and the SwiGLU activation function. Experiments on Ohsumed, MR, R52, and 20NG datasets confirm CoGraphNet’s effectiveness in complex classification tasks, demonstrating its superiority.